(untitled) (GIST – Education and Learning Research Journal, 2011)
We believe that world language education at all levels of instruction in the United States is in crisis. In this article, we respond to this crisis by proposing a spectrum of situatedness and its relation to five distinct pedagogical approaches in world language education. We help to elucidate this spectrum with classroom vignettes, illustrating different scenarios in world language education and some of their curricular components. We then conclude the article with the presentation of a tool to aid the reader in self-guiding and self-directing their own pedagogical practices. This tool is not conceptualized as a prescriptive option but rather as an instrument to help guide us in our academic endeavors. Our hope is that this notion of a spectrum helps us find a more precise terminology for characterizing our classrooms and our practices. We are arguing for a more balanced and reflective view of curriculum development in which teachers’ philosophies and pedagogic views are the major catalyst for programmatic development and change.